2015
DOI: 10.1371/journal.pone.0136639
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrode Material on the Voltage of a Tree-Based Energy Generator

Abstract: The voltage between a standing tree and its surrounding soil is regarded as an innovative renewable energy source. This source is expected to provide a new power generation system for the low-power electrical equipment used in forestry. However, the voltage is weak, which has caused great difficulty in application. Consequently, the development of a method to increase the voltage is a key issue that must be addressed in this area of applied research. As the front-end component for energy harvesting, a metal el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Thus, the corresponding booster and storage circuit for this device are under development. An energy system that includes other local environmental energy sources, such as solar irradiation [7,8,21], tree-based energy [22] and wind power energy [23,24], has also been developed to supplement power during summer power shortages.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the corresponding booster and storage circuit for this device are under development. An energy system that includes other local environmental energy sources, such as solar irradiation [7,8,21], tree-based energy [22] and wind power energy [23,24], has also been developed to supplement power during summer power shortages.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanism. An analysis of the plant as an energy source was conducted in [22,23] for Pachira and bigleaf maple trees, respectively. It is concluded that plant-bioenergy is heavily in uenced by environmental sunlight and moisture, and it approximately follows a periodic sinusoidal variation of 24 hours.…”
Section: Predictive-wakeupmentioning
confidence: 99%
“…This energy harvesting technique is feasible to be adapted in an area where living plants are abundantly available such as in farms or forest. It is shown by researchers that electrical energy can be tapped from a poplar tree ( Populus X Canadensis Moench ) using electrodes embedded into them [14]. In this research, the plant chosen is an Aloe Barbadensis Miller (Aloe Vera) which is from a succulent family of plants.…”
Section: Introductionmentioning
confidence: 99%